If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 3x = -21 Solving 9 + 3x = -21 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 3x = -21 + -9 Combine like terms: 9 + -9 = 0 0 + 3x = -21 + -9 3x = -21 + -9 Combine like terms: -21 + -9 = -30 3x = -30 Divide each side by '3'. x = -10 Simplifying x = -10
| 21/3=-9m | | y-118=-3 | | 9x+24y=27 | | (4)/(5)-12=(3)/(10)x | | -4x-5(x+3)=12 | | 15x-10(-2/15+1/5x)=-1 | | k+9.2=7.6 | | 20x+5y=0 | | -2y=x-10 | | y=x^2-10x+22 | | (4)/(5)-12=(3)/(10) | | 5y-5(2y-6)=15 | | -12x^2+17x+7=0 | | 7.32=13.53+2.81a | | -0.7=-7/9z | | 4(x^3-x+y)=0 | | 5r-19=-47+r | | x^3-21x^2+147x-343=729 | | g=70+3h | | 13m^2-15m=0 | | 5+y=7+y | | -y+138=247 | | 2(8y+7)-16y=14 | | (y+6)2=1 | | 5t/9-3/4=1/12+5t/8 | | 7-10/5 | | 4x^3+22x^2+30x= | | 1-6/5 | | H^2=33-4h | | 3/8(8t-4)=-2 | | 4(4y+3)(6y+8)= | | t/7=9/21 |